Mutant of herpes simplex virus type 1 conditionally able to transform thymidine kinaseless L cells to a tk+ phenotype. - Hughes, R G (1976)
After nitrous acid mutagenesis of herpes simplex virus type 1 (HSV-1), a mutant, 1093, was isolated which, during productive infection, induced very low levels of thymidine kinase (tk). The mutant virus was found, after UV irradiation, to be unable to transform L cells lacking tk (Ltk-) to a tk+ phenotype as chararcterized by growth of the cells in a modified HAT-selective medium containing 1.6 X 10(-5) M thymidine. Cells transformed by wild-type virus grew vigorously under the same conditions. The mutant was able to transform Ltk- cells if the medium contained 10(-3) M thymidine. These transformed cells maintained their conditional character and would not grow in low concentrations of thymidine in selective medium. Therefore, this mutant is conditional on the thymidine concentration in the selection medium in its ability to transform Ltk- cells to a tk+ phenotype. The conditionally transformed cells could be supertransformed with wild-type UV-irradiated HSV-1 to a phenotype which would grow in low-thymidine selective medium. The frequency of supertransformation closely approximated the frequency of transformation of Ltk- cells by wild-type virus. Supertransformation at high frequency could not be effected by mutant 1093 or the tk- mutant B2006. These results indicate that the presence of HSV-1 genetic information in HSV-1-transformed cells does not preclude the acquisition by these cells of at least one additional HSV-1 gene, that for tk.